Graphene reinforced copper-based composite material and preparation method thereof
Through the mechanochemical-in-situ conversion method, graphene is uniformly coated on the copper powder surface during the ball mill, solving the problem of uneven dispersion of graphene in the copper matrix, and improving the mechanical and electrical properties of graphene-reinforced copper-based composite materials , achieving higher quality graphitization effect.
Patent Information
- Application Number
- CN202411305036.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
During the preparation process of existing graphene-reinforced copper-based composites, the solid solubility between copper and carbon is insufficient, resulting in uneven dispersion of graphene in the copper matrix, serious agglomeration, affecting mechanical and electrical properties.
By using the mechanochemistry-in-situ conversion method, by mixing copper powder and organic carbon source for ball milling, the carbon source reacts on the surface of the copper powder by mechanical energy, forming a high-quality graphene reinforcement, reducing the production of amorphous carbon and improving the Graphitization degree.
The mechanical and electrical properties of graphene-reinforced copper-based composite materials are improved, and the structural integrity and mass of the body are enhanced. Compared with the thermal catalytic method, the formation of amorphous carbon is reduced and the conductivity is improved.
Smart Images

Figure CN119194147A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to a graphene-reinforced copper-based composite material and a preparation method thereof. Background Art
[0002] Graphene-enhanced copper-based composites have good mechanical and electrical properties. Currently, the methods for preparing graphene-copper-based composites mainly include external addition method and in-situ conversion method. Among them, the external addition method is to use various physical and chemical methods to evenly mix and disperse graphite / graphene / graphene oxide into a copper matrix to prepare a graphene-enhanced copper-based composite. However, since there is no solid solubility between copper and carbon, graphene cannot be well dispersed evenly in the copper matrix. When the local graphene content in the copper matrix is high, it will agglomerate under the guidance of van der Waals force, and the strengthening effect cannot be achieved. The in-situ conversion method is to prepare graphene-enhanced copper-based composites by catalyzing an organic carbon source on the copper surface at high temperature to produce graphene, so as to achieve uniform dispersion in the copper matrix, and the problem of uniform dispersion of the enhanced phase is solved. However, due to the limited catalytic area of copper, the catalytic amount of the carbon source is small, and most of it will be directly pyrolyzed to form amorphous carbon. The carbon reinforcement structure in the prepared graphene-enhanced copper-based composite is highly disordered and has a low crystallinity, thereby affecting the electrical conductivity and comprehensive performance of the composite. Summary of the invention
[0003] In view of this, the present invention provides a graphene-reinforced copper-based composite material and a preparation method thereof. The reinforcing phase in the graphene-reinforced copper-based composite material prepared according to the preparation method provided by the present invention has a high degree of graphitization, thereby improving the mechanical properties and electrical properties of the composite material.
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a graphene-reinforced copper-based composite material, comprising the following steps:
[0005] The copper powder and the organic carbon source are mixed and ball-milled to obtain a mixed material; the rotation speed of the ball mill is 500 to 2200 rpm;
[0006] The mixed material is sintered to obtain the graphene-reinforced copper-based composite material.
[0007] Preferably, the rotation speed of the ball mill is 800 to 1500 rpm, and the time of the ball mill is 15 to 1440 min.
[0008] Preferably, the ball-to-material ratio of the ball mill is 1:10 to 30:1.
[0009] Preferably, the grinding balls for ball milling include agate grinding balls, aluminum oxide grinding balls, zirconium oxide grinding balls, stainless steel grinding balls or tungsten carbide grinding balls;
[0010] The density of the grinding ball is 2.6-15.9 g / cm 3 ;
[0011] The average diameter of the grinding balls is 1 to 20 mm.
[0012] Preferably, the average particle size of the copper powder is 10 to 2000 μm.
[0013] Preferably, the organic carbon source includes a first organic carbon source and / or a second organic carbon source;
[0014] The first organic carbon source is an aromatic compound;
[0015] The second organic carbon source is an aliphatic compound.
[0016] Preferably, the mass percentage of copper powder in the mixed material is above 98%.
[0017] Preferably, the sintering temperature is 40-1000°C, the sintering holding time is 1-120 min, and the sintering pressure is 5-200 MPa.
[0018] Preferably, the sintering method includes spark plasma sintering, vacuum sintering, vacuum hot pressing sintering, microwave sintering or hot isostatic pressing sintering.
[0019] The present invention also provides a graphene-reinforced copper-based composite material prepared according to the preparation method described in the above technical solution
[0020] The present invention provides a method for preparing a graphene-enhanced copper-based composite material, comprising the following steps: mixing copper powder and an organic carbon source and ball milling to obtain a mixed material; the rotation speed of the ball mill is 500 to 2200 rpm; and the mixed material is sintered to obtain the graphene-enhanced copper-based composite material. The present invention proposes a mechanochemical-in-situ conversion method to prepare a graphene-enhanced copper-based composite material, in which the copper powder is refined during the ball milling process, and the organic carbon source undergoes a mechanochemical reaction on the surface of the copper powder, and is in-situ converted into an organic precursor with a larger molecular weight, and the surface of the copper powder is uniformly coated, thereby reducing the generation of amorphous carbon. Therefore, the graphene reinforcement in the graphene-enhanced copper-based composite material prepared according to the preparation method provided by the present invention has a more complete structure and better quality. Compared with the preparation of the graphene-enhanced copper-based composite material by the thermal catalytic in-situ conversion method, the preparation method provided by the present invention uses mechanical energy instead of thermal energy, so that the graphitization process is only generated when the copper collides, and the carbon source part that is not in contact with the copper is less amorphous carbonized. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The carbon Raman spectra of the mixed materials prepared in Examples 1 to 3 after corrosion;
[0022] Figure 2 This is a carbon TEM image of the mixed material prepared in Example 5 after corrosion;
[0023] Figure 3 This is a carbon TEM image of the graphene-enhanced copper-based composite material after corrosion prepared in Example 5;
[0024] Figure 4 This is a carbon Raman spectrum of the graphene-enhanced copper-based composite material prepared in Example 5 after corrosion;
[0025] Figure 5 The carbon Raman spectra of the mixed materials prepared in Example 7 and Comparative Example 1 after corrosion;
[0026] Figure 6 This is a comparison diagram of the Raman spectra of carbon and polyethylene after corrosion of the mixed material prepared in Comparative Example 2;
[0027] Figure 7 This is a graph showing the tensile test results of the graphene reinforced copper-based composite materials prepared in Comparative Example 3 and Example 5. DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a graphene-reinforced copper-based composite material, comprising the following steps:
[0029] The copper powder and the organic carbon source are mixed and ball-milled to obtain a mixed material; the rotation speed of the ball mill is 500 to 2200 rpm;
[0030] The mixed material is sintered to obtain the graphene-reinforced copper-based composite material.
[0031] In the present invention, unless otherwise specified, all materials are conventional commercially available products.
[0032] The present invention mixes copper powder and an organic carbon source and performs ball milling to obtain a mixed material. In the present invention, the average particle size of the copper powder is preferably 10 to 2000 μm, more preferably 13 to 100 μm, and further preferably 20 to 50 μm. In the present invention, the organic carbon source preferably includes a first organic carbon source and / or a second organic carbon source, more preferably a first organic carbon source or a second organic carbon source, and further preferably a first organic carbon source. In the present invention, the first organic carbon source is preferably an aromatic compound, more preferably diphenyl, triphenyl, polyphenyl, pyrene, fluorene, coronene, pyridine, polystyrene or polyphenylene, and further preferably biphenyl. In the present invention, the polyphenyl is preferably diphenyl, terphenyl or quaternary biphenyl, and more preferably terphenyl.
[0033] In the present invention, the second organic carbon source is preferably an aliphatic compound, more preferably one of polyethylene, polypropylene, polymethyl methacrylate and polyacrylonitrile, and further preferably polyethylene.
[0034] In the present invention, the mass percentage of the copper powder in the mixed material is preferably above 98%, more preferably 99 to 99.9%.
[0035] In the present invention, the rotation speed of the ball mill is 500-2200rpm, preferably 800-1500rpm, more preferably 800-1440rpm; the ball milling time is preferably 15-1440min, more preferably 30-120min, and further preferably 30-60min. In the present invention, the ball-to-material ratio of the ball mill is preferably 1:10-30:1, more preferably 7:1-30:1, and further preferably 7:1-10:1. In the present invention, the grinding balls for ball milling preferably include agate grinding balls, aluminum oxide grinding balls, zirconium oxide grinding balls, stainless steel grinding balls or tungsten carbide grinding balls, more preferably zirconium oxide grinding balls or stainless steel grinding balls; the average diameter of the grinding balls is preferably 1-20mm, more preferably 1mm, 3mm, 5mm, 10mm or 20mm. In the present invention, the density of the grinding balls is preferably 2.6-15.9g / cm 3 When the grinding ball is a tungsten carbide grinding ball, the density of the grinding ball is preferably 15.9 g / cm 3 When the grinding ball is a zirconia grinding ball, the density of the grinding ball is preferably 5.85 g / cm 3 When the grinding balls are stainless steel grinding balls, the density of the grinding balls is preferably 7.7 to 8 g / cm 3 . In the present invention, the ball milling is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably an inert gas; the inert gas is preferably argon or helium, and more preferably argon. In the present invention, the material of the ball milling jar for ball milling is preferably agate, stainless steel, zirconium oxide, tungsten carbide or resin. In the present invention, the organic carbon source undergoes dehydrogenation polymerization on the surface of the copper powder during the ball milling process, is converted into an organic precursor in situ, and is uniformly coated on the surface of the copper powder. The present invention limits the ball milling conditions within the above range, which is conducive to providing the energy required for the chemical reaction during the ball milling process, thereby improving the graphitization efficiency.
[0036] After obtaining the mixed material, the present invention sintered the mixed material to obtain the graphene-reinforced copper-based composite material. In the present invention, the sintering temperature is preferably 40 to 1000°C, more preferably 100 to 800°C; the heating rate to the temperature required for sintering is preferably 90 to 110°C / min, more preferably 100°C / min. In the present invention, the sintering holding time is preferably 1 to 120min, more preferably 5 to 20min; the sintering pressure is preferably 5 to 200MPa, more preferably 40 to 100MPa. In the present invention, the sintering method preferably includes spark plasma sintering (SPS), vacuum sintering, vacuum hot pressing sintering, microwave sintering or hot isostatic pressing sintering, more preferably spark plasma sintering. The present invention preferably places the mixed material in a mold for sintering, and the material of the mold is preferably graphite.
[0037] In the present invention, after sintering, the process preferably further comprises: cooling the sintered system to room temperature; the room temperature is preferably 25-30° C. In the present invention, the cooling rate is preferably 90-110° C. / min, more preferably 100° C. / min.
[0038] The present invention also provides a graphene-enhanced copper-based composite material prepared by the preparation method described in the above technical solution. In the present invention, the yield strength of the graphene-enhanced copper-based composite material is preferably 130 MPa, and the electrical conductivity is preferably 93.95% IACS.
[0039] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0040] Example 1
[0041] In a ball mill made of zirconium oxide, add 3g of copper powder with an average particle size of 15μm, 1.5mg of terphenyl and 30g of a granular material with an average diameter of 10mm and a density of 5.85g / cm 3 The zirconia grinding balls are placed in a ball mill in an argon protective atmosphere (the single ball milling time is set to 15 min, the rotation speed is 800 rpm, and the number of cycles is set to 1 time and the total ball milling time is 15 min) for ball milling to obtain a mixed material;
[0042] 30 g of the mixed material was placed in a graphite mold with a diameter of 30 mm and placed in a spark plasma sintering furnace. The temperature was increased to 800°C at a heating rate of 100°C / min. After sintering for 5 minutes at a temperature of 800°C and a pressure of 40 MPa, the temperature was reduced to 30°C at a cooling rate of 100°C / min to obtain a graphene-reinforced copper-based composite material.
[0043] Embodiments 2 to 7
[0044] A graphene-reinforced copper-based composite material was prepared according to the method of Example 1, with the differences being referred to Table 1.
[0045] Table 1 Conditions and parameters for preparing graphene-enhanced copper-based composite materials in Examples 1 to 7
[0046]
[0047] Comparative Example 1
[0048] 10 g of copper powder was placed in a three-necked flask, 20 mL of xylene and 3 mg of polyethylene were added to the three-necked flask, heated to 120° C. and stirred for 10 min, cooled to room temperature, and filtered to obtain a mixture; the obtained mixture was heated to 800° C. at a heating rate of 10° C. / min in a hydrogen-argon mixed gas with a hydrogen content of 5% (gas flow rate of 200 sccm) and kept warm for 10 min to obtain a composite material.
[0049] Comparative Example 2
[0050] 8 g of copper powder with an average particle size of 15 μm, 1.5 mg of polyethylene and 240 g of tungsten carbide grinding balls with an average diameter of 10 mm were added to a ball mill made of tungsten carbide, and the ball mill was placed in a ball mill in a vacuum (the single ball milling time was set to 30 min, the rotation speed was set to 400 rpm, and the number of cycles was set to 24 times with a total ball milling time of 720 min) for ball milling to obtain a mixed material;
[0051] A graphene-reinforced copper-based composite material was prepared according to the method of Example 1.
[0052] Comparative Example 3
[0053] 3 g of copper powder with an average particle size of 15 μm and 30 g of zirconium oxide grinding balls with an average diameter of 10 mm were added to a ball mill made of zirconium oxide, and the ball mill was placed in a ball mill in an argon protective atmosphere (the single ball milling time was set to 30 min, the rotation speed was 800 rpm, and the number of cycles was set to 1 time with a total ball milling time of 15 min) for ball milling to obtain a mixed material;
[0054] The mixed material was sintered in the manner of Example 1 to obtain a pure copper comparison sample.
[0055] The mixed material prepared in Examples 1 to 3 (the mass percentage of the organic carbon source in the mixed material is 0.05%) was soaked in a 10% nitric acid aqueous solution for 48 hours and then filtered to obtain corroded carbon. The corroded carbon was detected using a Raman spectrometer to obtain a Raman spectrum, as shown in FIG. Figure 1 As shown. Figure 1It can be seen that the Raman characteristic peaks of graphene are the D peak at 1350-1370 cm and the G peak at 1580-1600 cm. It can be seen from the Raman peaks that the characteristic peaks of the raw materials are weakened and disappear, while the D peak and G peak representing the graphite material appear, indicating that the organic carbon source is graphitized under the mechanical energy of grinding. The same test results are obtained for the mixed materials prepared in Examples 4 to 7, and the results are the same as those in Example 1.
[0056] The mixed material prepared in Example 5 (the mass percentage of the organic carbon source in the mixed material is 0.05%) was immersed in a nitric acid aqueous solution with a mass concentration of 10% for 48 hours and then filtered to obtain corroded carbon. The corroded carbon was detected using a transmission electron microscope to obtain a TEM image, as shown in FIG. Figure 2 As shown. Figure 2 The carbon lattice fringes can be clearly observed, indicating that the graphene converted from the carbon source has good crystallinity; the lattice fringes are measured to be 0.36nm, which is close to the interplanar spacing of the graphene (002) crystal plane of 0.34nm, which further illustrates that the conversion product of terphenyl is graphene-like structured carbon, and graphene appears in terphenyl and copper powder.
[0057] The graphene-enhanced copper-based composite material prepared in Example 5 (the mass percentage of the organic carbon source in the mixed material is 0.1%) was immersed in a nitric acid aqueous solution with a mass concentration of 10% for 48 hours and then filtered to obtain the corroded carbon. The corroded carbon was detected using a transmission electron microscope to obtain a TEM image, as shown in FIG. Figure 3 As shown. Figure 3 The wrinkles of the carbon film can be observed at low magnification and it can be seen that the carbon layer is relatively thin. Clear lattice fringes can be obtained under high resolution observation, and the crystal plane spacing is about 0.34nm, indicating that graphene is contained in the graphene-reinforced copper-based composite material.
[0058] The graphene-enhanced copper-based composite material prepared in Example 5 (the mass percentage of the organic carbon source in the mixed material is 0.1%) was immersed in a nitric acid aqueous solution with a mass concentration of 10% for 48 hours and then filtered to obtain corroded carbon. The corroded carbon was detected using a Raman spectrometer to obtain a Raman spectrum, as shown in FIG. Figure 4 As shown. Figure 4 It can be seen that the carbon after corrosion has a 2D peak and less overlapping D and G peaks, indicating that the organic carbon source has a high degree of graphitization and the quality of the reinforcing phase graphene in the graphene-reinforced copper-based composite material is good.
[0059] The mixed materials prepared in Example 7 and Comparative Example 1 were immersed in a nitric acid aqueous solution with a mass concentration of 10% for 48 hours and then filtered to obtain corroded carbon. The corroded carbon was detected using a Raman spectrometer to obtain a Raman spectrum, as shown in FIG. Figure 5 As shown. Figure 5It can be seen that the D peak and G peak of the corroded carbon overlap less than those of thermal catalysis, indicating that compared with thermal catalysis, the graphene prepared by mechanochemical method will convert amorphous carbon, further indicating that the mechanochemical method can prepare higher quality graphene.
[0060] The mixed material prepared in Comparative Example 2 was immersed in a nitric acid aqueous solution with a mass concentration of 10% for 48 hours and then filtered to obtain the corroded carbon. The corroded carbon and polyethylene raw material were tested using a Raman spectrometer to obtain a Raman spectrum, as shown in FIG. Figure 6 Polyethylene hardly undergoes transformation, which indicates that there is a minimum excitation energy for mechanochemical reactions. When the energy is insufficient to reach the activation energy of the reaction, the reaction cannot be caused by prolonging the time.
[0061] The tensile test results of the graphene-reinforced copper-based composite material prepared by the pure copper comparison sample of Comparative Example 3 and Example 5 are as follows: Figure 7 As shown. Figure 7 The mechanical properties of the material are analyzed as follows: the elongation of comparative example 3 is 32.13%, and the elongation of embodiment 5 is 22.96%. Although the elongation of embodiment 5 is lower than that of comparative example 3, it still maintains high plasticity; the yield strength of comparative example 3 is 114.7MPa, and the yield strength of embodiment 5 is 130.5MPa. The tensile strength of comparative example 3 is 244.1MP, and the tensile strength of embodiment 5 is 266.5MPa. The composite material provided by the present invention has good mechanical properties, indicating that graphene improves the mechanical properties of the material.
[0062] The conductivity of Examples 4 to 6 and Comparative Example 3 was tested, and the conductivity results obtained are listed in Table 2.
[0063] Table 2 Electrical conductivity of graphene-enhanced copper-based composite materials of Examples 4 to 6 and pure copper comparison sample of Comparative Example 3
[0064]
[0065] It can be seen from Table 2 that the electrical conductivity of the composite material provided by the present invention increases with the increase of carbon content.
[0066] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a graphene-reinforced copper-based composite material, comprising the following steps: The copper powder and the organic carbon source are mixed and ball-milled to obtain a mixed material; the rotation speed of the ball mill is 500 to 2200 rpm; The mixed material is sintered to obtain the graphene-reinforced copper-based composite material.
2. The preparation method according to claim 1, characterized in that: The rotation speed of the ball mill is 800-1500 rpm, and the time of the ball mill is 15-1440 min.
3. The preparation method according to claim 1 or 2, characterized in that: The ball-to-material ratio of the ball mill is 1:10 to 30:
1.
4. The preparation method according to claim 3, characterized in that: The grinding balls for ball milling include agate grinding balls, aluminum oxide grinding balls, zirconium oxide grinding balls, stainless steel grinding balls or tungsten carbide grinding balls; The density of the grinding ball is 2.6-15.9 g / cm 3 ; The average diameter of the grinding balls is 1 to 20 mm.
5. The preparation method according to claim 1, characterized in that: The average particle size of the copper powder is 10 to 2000 μm.
6. The preparation method according to claim 1, characterized in that: The organic carbon source includes a first organic carbon source and / or a second organic carbon source; The first organic carbon source is an aromatic compound; The second organic carbon source is an aliphatic compound.
7. The preparation method according to claim 1, 5 or 6, characterized in that: The mass percentage of copper powder in the mixed material is above 98%.
8. The preparation method according to claim 1, characterized in that: The sintering temperature is 40-1000° C., the sintering heat preservation time is 1-120 min, and the sintering pressure is 5-200 MPa.
9. The preparation method according to claim 1 or 8, characterized in that: The sintering method includes spark plasma sintering, vacuum sintering, vacuum hot pressing sintering, microwave sintering or hot isostatic pressing sintering.
10. A graphene-reinforced copper-based composite material prepared according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of graphene reinforced copper-based composite material
CN112981159A
Preparation method of copper / graphene composite wire
CN114530291A
Preparation method of graphene reinforced copper-based composite material
CN117286363A
Method for preparing graphene / copper composite powder and composite material by utilizing microwaves
CN117604302A
Method for preparing enhanced graphene / copper composite material through in-situ reduction method
CN117626041A
